Penile ossification of the entire penile shaft found incidentally on pelvic x-ray - El Hasbani, Georges (Urol Case Rep, 2019)
Penile ossification, a rare condition, has been linked traditionally to Peyronie's disease (PD) despite the presence of other less common etiologies. The ossification takes place usually in the mid-shaft of the penis with few cases reporting involvement of the entire shaft. Ultrasound has been the method of choice to demonstrate plaque calcifications. Medical and surgical treatment options exist depending on the extent of ossification and symptoms. This case report discusses the presence of ossification in the entire penile shaft which has been found incidentally on a pelvic x-ray in a patient presenting to the emergency department for a trauma of the knee.